DEVELOPING STUDENT’S SELF-ESTEEM IN SPEAKING USING GAMIFICATION APPROACH OF KINDERGAR-TEN STUDENT IN ESL CLASS - anita anggraeni; Anggy Pradita (Tunas Siliwangi, 2023)
Children interact with other children, their parents, and other adults as they acquire language. A child can readily acquire two or more languages at once as long as they are conversing with speakers of those languages on a regular basis.. The purpose of this study is to investigate the connection between the use of offline games and young students' self-esteem in speaking English. The researchers' interpretation of the children's written material served as the foundation for the majority of this study's conclusions. In terms of enhancing self-esteem, the data analysis showed numerous evident benefits for all students. The students were free to exercise their independence and display qualities about themselves. ESL students had the same opportunity to compete with their classmates for the limited time that they took part in these activities. This study used a qualitative approach and conducted a pilot test on pre-school students. This research was conducted at Learning Tots Kindergarten located on Sri pohaci Street, Bandung, Indonesia. The study was conducted on 19 students of Learning Tots Kindergarten. The students were given time to play for 30-60 minutes every day for 2 weeks. The games included matching, bingo, and charades. The study was distinctive in that the students produced written summaries of the game events. The basis of this study's data gathering is qualitative information obtained from observations and conducted interviews. This research was conducted using qualitative methods. Where data analysis is based on interviews with research subjects regarding the impression they feel after playing the game. Furthermore, the researcher also saw and analyzed the students' behavior through observation techniques